Divergent neighbors: corporatism and climate policy networks in Finland and Sweden. Issue 6 (19th September 2019) - Gronow, Antti; Ylä-Anttila, Tuomas; Carson, Marcus; Edling, Christofer
ABSTRACT: Previous research has suggested that corporatist polities tend to enact more ambitious environmental policies than others. Here it is argued that the macro concept of corporatism can be dissected into three components: inclusiveness, consensualism and strength of tripartite organisations. These components of corporatism can be measured at the meso-level of policy networks. It is proposed that inclusiveness and consensualism are related to ambitious climate policy but exclusive tripartite coalitions can be detrimental for the ambitiousness of climate policy. This argument is backed by evidence from policy network surveys in two similar corporatist countries where climate change policies diverge: Sweden, where policies are ambitious, and Finland, where they are less so. It is found that in Sweden the climate change policy network is more consensual and slightly more inclusive, while in Finland tripartite organisations play a strong role.